2011
DOI: 10.1124/jpet.111.188078
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Fibrosis Progression in CCl4-Treated Rats: Role of the Hepatic Endocannabinoid and Apelin Systems

Abstract: Endocannabinoids behave as antifibrogenic agents by interacting with cannabinoid CB2 receptors, whereas the apelin (AP) system acts as a proangiogenic and profibrogenic mediator in the liver. This study assessed the effect of long-term stimulation of CB2 receptors or AP receptor (APJ) blockade on fibrosis progression in rats under a non-discontinued fibrosis induction program. The study was performed in control and CCl 4 -treated rats for 13 weeks. Fibrosis-induced rats received a CB2 receptor agonist (R,S)-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…The in vivo effects of PDGFR inhibitors are more complex, based on the crosstalk with other angiogenic factors [21,22]. We have recently reported that the stimulation of CB2 receptors, as well as the blockade of the hepatic apelin system activity, is able to attenuate collagen deposition in CCl 4 -treated rats through common mechanisms, such as the inhibition of PDGFRb expression [15]. In the current study, we investigated the role of PDGFRb in the physiopathological alterations that take place along the course of CCl 4 -induced experimental liver disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo effects of PDGFR inhibitors are more complex, based on the crosstalk with other angiogenic factors [21,22]. We have recently reported that the stimulation of CB2 receptors, as well as the blockade of the hepatic apelin system activity, is able to attenuate collagen deposition in CCl 4 -treated rats through common mechanisms, such as the inhibition of PDGFRb expression [15]. In the current study, we investigated the role of PDGFRb in the physiopathological alterations that take place along the course of CCl 4 -induced experimental liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently described that PDGFRb mRNA is overexpressed in the liver of rats subjected to chronic inhalation of carbon tetrachloride (CCl 4 ) as compared to control animals. Moreover, we have reported the antifibrogenic effects of endocannabinoids and apelin, which are associated with the inhibition of PDGFRb expression [15].…”
Section: Introductionmentioning
confidence: 98%
“…Endocannabinoids are bioactive lipids that act on cannabinoid receptors, CB 1 R and CB 2 R, that also recognize and mediate the effects of marijuana (16). Endocannabinoids acting via CB 1 R promote fibrosis progression in multiple organs, including liver (17)(18)(19)(20)(21), kidney (22,23), heart (24), and skin (25), and CB 1 R has been linked to radiation-induced PF in mice (26). In addition to promoting fibrosis, activation of CB 1 R is proinflammatory in chronic inflammatory diseases (27,28), whereas the brain-penetrant CB 1 R antagonist/inverse agonist rimonabant mitigates liver fibrosis in animal models (17).…”
Section: Introductionmentioning
confidence: 99%
“…Both cannabinoid receptor-1 (CB 1 ) and cannabinoid receptor-2 (CB 2 ) were recently implicated in pathogenesis of skin (7)(8)(9)(10), liver (11)(12)(13)(14), cardiac (15), and renal (16) fibrotic proliferative diseases. However, the role of the endocannabinoid system in pulmonary fibrogenesis remains enigmatic.…”
mentioning
confidence: 99%